Nutrition in the neurocritical care unit - Tripathy, Swagata (Journal of Neuroanaesthesiology and Critical Care, 2015)
The aim of intensive care is to support the physiology of the body till the treatment or the reparative process of the body kicks in to the rescue. Maintaining an adequate nutrition during this period is of vital importance to counteract the catabolic effect of the critical disease process. The guidelines for nutritional care in the neuro intensive care unit (ICU) are sparse. This article collates the current evidence and best practice recommendations as applicable to the critically ill patient in the neuro ICU. The use of screening tests to identify patients at a risk of malnutrition and related complications is presently recommended for all patients with an emphasis on early initiation of caloric support. Over-aggressive feeding in an attempt to revert the catabolic effects of critical illness have not proven beneficial, just as the attempts to improve patient outcomes by altering the routes of nutrition administration. Special patient population such as traumatic brain injury, stroke, subarachnoid haemorrhage or spinal cord injury may have varying nutritional requirements; individualised approach in the neurocritical ICU with the help of the intensivist, nutritionist and pharmacology team may be of benefit.
Keywords: Neurointensive care; nutrition; nutrition screening tools